Analisis Alokasi Sumberdaya Utama Industri Kecil Mebel dan Implikasinya terhadap Kurva Penawaran Normatif (Studi Kasus di Daerah Sekitar Program Pengelolaan Hutan Bersama Masyarakat (PHBM) Pasuruan Jawa Timur) - -, Nasikh (Jurnal Aplikasi Manajemen, 2009)
Nowdays, there is a significant increase in the number of profits small industry exist bringing on tighter competitive situation. For that reason, effeciency small industries are required to improve themselves continuously. One of the ways to do that is by measuring the allocation main resources accurately. The main aim of this research generally are to analyze of the allocation furniture main resources, to analyze the combination of furniture products that can be produced by the craftsman, to analyze normative supply curve.This research was done in Pasuruan. The respondents were consisting of 49 furniture craftsman. The result of this research showed that the usage of furniture main resources (teak and capital) had been optimal. Labor is furniture main resources had not been optimal yet. The combination of furniture products that can be developed optimally by the craftsman generally are dressing table, 1 door wardrobe, 1 meter of buffet, 2 door wardrobe, 2 meter of buffet, 3 door wardrobe and bed, table, and chair. Normative supply curve is perfect inelastis.Keywords: The allocation main resources, small industries, normative supply curve, forest management program